Preserving anonymity in eVoting using authentication techniques: a review / Nurain Nabilah Salehuddin, Siti Rahayu Abdul Aziz and Shahadan Saad - Salehuddin, Nurain Nabilah; Abdul Aziz, Siti Rahayu; Saad, Shahadan (2022)
The use of an electronic voting system allows voters to cast ballots over a computer network. As a result, voters will be able to participate in elections without having to travel to polling stations, which is more convenient and efficient. The confidentiality of voter information is one of the criteria that is considered essential and desirable. Electronic voting protocols must ensure voter anonymity as a fundamental requirement in order to provide adequate protection for voters' privacy. This ensures that a specific vote cannot be traced back to any voter. To put it another way, it is not possible to disclose or demonstrate a connection between voters and their votes. The requirement for voters' anonymity is what differentiates electronic voting from other types of electronic applications. It's possible that voters won't reveal their true preferences if their anonymity is threatened. As a result, the primary concentration of this article will be on the problem of maintaining voters' anonymity within electronic voting systems. A few concerns revolve around the design of the system, and two of those concerns are the voters' anonymity in the database records and the authenticity of the vote that is cast to the system. It is planned to implement a hashing algorithm on the data stored in the database to protect the anonymity of the voters. The method of authentication that will be used will be Multifactor Authentication (MFA), which will use user identification and a One-Time Password (OTP). It is anticipated that the project will contribute toward satisfying the demand for a secure and reliable electronic voting system.